Kontribusi Orang Tua Tentang Cara Anak Memahami Keberagaman Dalam Interaksi Sosial Anak Usia Dini - Anggraeni, Ira (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
The aim of this study is to analyze the contribution of parents in helping children understand diversity in social interactions. This study uses a survey research method with a questionnaire data collection technique. From the results of the study, two major themes were found that are related to the contribution of parents in helping children understand diversity in social interactions of young children. The first theme is the awareness of parents about multiculturalism, which includes an understanding of cultural and value diversity in society, as well as a willingness to recognize and appreciate these differences. The second theme is the contribution of parents in the way children understand diversity in social interactions, which includes parental support in introducing children to social and cultural diversity, as well as facilitating positive experiences in social interactions involving cultural and value differences. Therefore, parents should play an active role in educating their children and ensure that they introduce their children to social and cultural diversity from an early age.